A combined laboratory and synchrotron in-situ photoemission study of the rutile TiO2 (110)/water interface. (23rd February 2021) - Byrne, Conor; Zahra, Khadisha M; Dhaliwal, Simran; Grinter, David C; Roy, Kanak; Garzon, Wilson Q; Held, Georg; Thornton, Geoff; Walton, Alex S
Abstract: In-situ analysis of the TiO2 /water interface via near ambient pressure–x-ray photoelectron spectroscopy (NAP–XPS) is demonstrated in both a lab based system (NAP-cell configuration) and synchrotron endstation (backfill configuration). Ultra-thin wetting layers of liquid water (∼10 nm) are formed on a rutile TiO2 surface with minimal contamination present in addition to unique insight during the growth of the liquid films as indicated via NAP–XPS, in-situ sample temperature and background vapour pressure monitoring. Chemical changes at the solid/liquid interface are also demonstrated via healing of Ti 3+ surface defect states. Photon depth profiling of the as grown liquid layers indicate that the formed films are ultra-thin (∼10 nm) and likely to be continuous in nature. This work demonstrates a novel and flexible approach for studying the solid/liquid interface via NAP–XPS which is readily integrated with any form of NAP–XPS system, thereby making a critical interface of study available to a wide audience of researchers for use in operando electrochemical and photocatalytic research.